Upaya Meningkatkan Perencanaan Karir Siswa SMA melalui Pendekatan Konseling Trait and Factor - Izzulhaq, Daffa; Fauzan, Hafizt; Febriansyah, Bilal Eleazar (Lembaga Yasin AlSys, 2024)
Wise career planning significantly impacts the course of one's life; therefore, such decisions must be carefully considered. Career guidance for students is necessary. Career guidance can be defined as the counselor's effort to assist students in understanding themselves and their surroundings in the process of career selection and development. Therefore, the selection of counseling approaches or techniques should also be considered. Trait and factor is one approach that can be applied. The method used in this research is qualitative research, employing literature review as a means to collect data from relevant literature or journals related to the research topic as the primary source of data. The findings of this research indicate that the trait and factor approach can help students identify and understand factors related to their personality and abilities, facilitating a more effective career planning process aligned with their potential and interests. To maximize this approach, six steps must be followed: analysis, synthesis, diagnosis, prognosis, counseling, and follow-up.This theory has advantages in providing easy access for clients to obtain job-related information, including necessary requirements. However, it also has its drawbacks as it tends to overlook the role of emotional intelligence in the decision-making process of the client.